Metasurface-Coated Liquid Microlens for Super Resolution Imaging - Tongkai Gu; Kang Wang; Anjiang Cai; Fan Wu; Yasheng Chang; Haiyan Zhao; Lanlan Wang (Micromachines)
Inspired by metasurfaces’ control over light fields, this study created a liquid microlens coated with a layer of Au@TiO2, Core-Shell nanospheres. Utilizing the surface plasmon resonance (SPR) effect of Au@TiO2, Core-Shell nanospheres, and the formation of photonic nanojets (PNJs), this study aimed to extend the imaging system’s cutoff frequency, improve microlens focusing, enhance the capture capability of evanescent waves, and utilize nanospheres to improve the conversion of evanescent waves into propagating waves, thus boosting the liquid microlens’s super-resolution capabilities. The finite difference time domain (FDTD) method analyzed the impact of parameters including nanosphere size, microlens sample contact width, and droplet’s initial contact angle on super-resolution imaging. The results indicate that the full width at half maximum (FWHM) of the field distribution produced by the uncoated microlens is 1.083 times that of the field distribution produced by the Au@TiO2, Core-Shell nanospheres coated microlens. As the nanosphere radius, droplet contact angle, and droplet base diameter increased, the microlens’s light intensity correspondingly increased. These findings confirm that metasurface coating enhances the super-resolution capabilities of the microlens.